The Therapeutic Potential of Targeting Key Signaling Pathways as a Novel Approach to Ameliorating Post-Surgical Adhesions - Ensan, Behzad; Bathaei, Parsa; Nassiri, Mohammadreza; Khazaei, Majid; Hassanian, Seyed M.; Abdollahi, Abbas; Ghorbani, Hamid Reza; Aliakbarian, Mohsen; Ferns, Gordon A.; Avan, Amir (Current Pharmaceutical Design, 2022)
Background: Peritoneal adhesions (PA) are a common complication of abdominal operations. A growing body of evidence shows that inhibition of inflammation and fibrosis at sites of peritoneal damaging could prevent the development of intra-abdominal adhesions. Methods: A search of PubMed, Medline, CINAHL and Embase databases was performed using the keywords ‘postsurgical adhesion’, ‘post-operative adhesion’, ‘peritoneal adhesion’, ‘surgery-induced adhesion’ and ‘abdominal adhesion’. Studies detailing the use of pharmacological and non-pharmacological agents for peritoneal adhesion prevention were identified, and their bibliographies were thoroughly reviewed to identify further related articles. Results: Several signaling pathways, such as tumor necrosis factor-alpha, tissue plasminogen activator, and type 1 plasminogen activator inhibitor, macrophages, fibroblasts, and mesothelial cells play a key part in the development of plasminogen activator. Several therapeutic approaches based on anti-PA drug barriers and traditional herbal medicines have been developed to prevent and treat adhesion formation. In recent years, the most promising method to prevent PA is treatment using biomaterial-based barriers. Conclusion: In this review, we provide an overview of the pathophysiology of adhesion formation and various agents targeting different pathways, including chemical agents, herbal agents, physical barriers, and clinical trials concerning this matter.
Keywords: peritoneal adhesions